Tool use and hand preference in Macaca fascicularis aurea. - Tan, Virnice Pinlin. (2010)
Tool use among long-tailed macaques in natural environments has been limited to anecdotal reports. The present study investigated the extent to which macaques on Piak Nam Yai Island, Thailand, take into account properties of tools. Sex differences in tool use and feeding behavior are examined. Additionally, as many studies on population-level handedness have produced ambiguous results, handedness is also explored. Results suggest that Macaca fascicularis aurea actively select tools of appropriate weight to crack open food items and that they may be naturally and spontaneously choosing stones based on their properties and characteristics of food items. Population-level handedness and sex differences also exist. We further discuss implications and limitations of our study and subsequently, offer suggestions for current and future research.